Factors affecting the choice of contraceptives among married women of reproductive age (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Family planning refers to a conscious effort by a couple to limit or space the number of children through the use of contraceptive methods. This study aims to identify the factors affecting the choice of contraceptives among married women of reproductive age.Method: A descriptive cross-sectional study design was adopted among 326 samples at Family Planning Sansthagat Clinic, Lalitpur from July to September 2017. Face-to-face interview using a structured questionnaire was used for data collection. Association between married women’s socio-demographic variables with the factors affecting the choice of contraceptives were analyzed. SPSS 16 was used for statistical analysis. Ethical approval was taken from the Institutional Review Board of Tribhuvan University, Institute of Medicine.Result: The study revealed that 100% of the respondents had known about condoms and pills as contraceptives methods. 314(96.3%) of the respondents were using a modern method of family planning. Among them, 186(59.2%) were using an implant. One hundred and seventy-three women (53.1%) had started using contraceptives after the birth of their first child. 142(43.6%) stated that they discontinued using some contraceptives in the past. The main reason for discontinuation was due to side effects of 70(49.3%). Purposes of using contraceptives, preference for child sex are the significant factors for the choice of contraceptives.Conclusion: This study result revealed that most of the respondents were using a modern method and among them, Implant was the most practiced family planning method. Women’s active involvement in decision-making regarding the use of contraceptives can play an important role in its utilization.